'Oh, Oh Rodeo!!': American Cowboys and Post-Independence Ireland1. Issue 1 (December 2022) - Heffernan, Conor
In 1924 Tex Austin, an American showman, brought his world travelling Rodeo to Croke Park in Dublin. Coming at a time of significant social and political upheaval in Ireland, Austin's rodeo promised an entirely new kind of spectacle which was free from imperial or British connotations. Austin's rodeo, and cowboy paraphernalia in general, seemed largely immune from cultural suspicions despite the fact that few citizens knew what a rodeo actually entailed. The purpose of the present article is twofold. First it provides a detailed examination of Tex Austin's Dublin Rodeo, and a growing proliferation of cowboy culture in interwar Ireland. Second, it uses Austin's Rodeo and its aftermath, to discuss the rise of cowboy masculinities in Ireland. Done to highlight the multiplicity of masculine identities in the Free State, the article discusses the appeal of cowboy inspired masculinity in Ireland, as well as the mediums through which it passed. Such an identity was not all encompassing but it did exist, and was sustained by the entertainment and leisure industry. Its study reiterates the need for more work on the various pressures and influences brought to bear on Irish masculinity.